CPC-137 The Percentage of Medicines Orders For Intermittent Treatment That Are "reviewed" by a Pharmacist For "safe Prescribing". (12th March 2013) - Ryan, B; Ging, P; Brown, J; Edwards, R; Meegan, C
Abstract : Background: A multidisciplinary panel chose the percentage of medicines orders for intermittent therapy that have been reviewed by a pharmacist for safe prescribing as a valid and feasible performance indicator for the Mater Misericordiae University Hospital (MMUH) clinical pharmacy service. Fatalities have been reported due to errors in the prescribing and administration of intermittent medicines. Pharmacists have a recognised role in clearly communicating intermittent medicines orders. Purpose: To develop a performance indicator descriptor and data collection tool for the chosen indicator. To measure the percentage of medicines orders for intermittent medicines that had been reviewed by a pharmacist for safe prescribing. Materials and Methods: A performance indicator descriptor and data collection tools were developed and piloted. 100 in-patient beds were randomly selected. All patients supplied with methotrexate or an erythropoiesis stimulating agent 14 days prior to data collection were included. Pharmacists were not informed data collection was taking place. An independent pharmacist collected the data to reduce bias. Data collection was checked for inter-rater reliability. Intermittent medicines were defined as 'safely prescribed' if the day(s) of the week that the medicine was to be taken were stated and the day(s) when the medicine was not to be taken were crossed out in the administration section of the drug chart. Medicines orders were classified as fully 'reviewed' by a pharmacist when (in addition to checking the dose and frequency of the prescribed medicine) the above parameters, if not entered by the prescriber, were completed by the pharmacist as outlined by the Clinical Pharmacy Services Standard Operating Procedure (SOP). Results: 79% (48/61) of medicines orders for intermittent medicines were 'reviewed' by a pharmacist for 'safe prescribing'. 21% (13/61) had been signed as clinically reviewed but did not fully meet the criteria of a safely prescribed intermittent medicines. 11% (7/61) were prescribed as per MMUH prescribing policy and did not require further endorsements by a clinical pharmacist. Conclusions: A valid tool was developed that measured the baseline performance of the MMUH clinical pharmacy service for the safe prescribing of intermittent medicines. Clarification of the clinical pharmacy services SOP will lead to improved performance as pharmacists had varying interpretations of the SOP. No conflict of interest.